2019
DOI: 10.1101/650556
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Higher Meta-cognitive Ability Predicts Less Reliance on Over Confident Habitual Learning System

Abstract: Many studies on human and animals have provided evidence for the contribution of goal-directed and habitual valuation systems in learning and decision-making. These two systems can be modeled using model-based (MB) and model-free (MF) algorithms in Reinforcement Learning (RL) framework.Here, we study the link between the contribution of these two learning systems to behavior and meta-cognitive capabilities. Using computational modeling we showed that in a highly variable environment, where both learning strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…People with lower average confidence had a weaker model-free contribution to their decisions. This is consistent with findings in Ershadmanesh et al (2019), where authors showed that there is a negative correlation between the model-free component of decision and memory meta-metacognition. Since the two-step decision-making task is designed in a way that you could not have a better than random performance (Akam et al, 2015;Kool et al, 2016), it can be argued that people with lower confidence understood this fact better and were more meta-cognitive.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…People with lower average confidence had a weaker model-free contribution to their decisions. This is consistent with findings in Ershadmanesh et al (2019), where authors showed that there is a negative correlation between the model-free component of decision and memory meta-metacognition. Since the two-step decision-making task is designed in a way that you could not have a better than random performance (Akam et al, 2015;Kool et al, 2016), it can be argued that people with lower confidence understood this fact better and were more meta-cognitive.…”
Section: Discussionsupporting
confidence: 92%
“…The above proposal is in line with Frith and Frith (2012)'s discussion about exertion of control over automatic behavior via meta-cognitive processes. Ershadmanesh et al (2019)'s result confirm our proposal, too. They show a positive relationship between the proportion of model-based relative to model-free behavior and self-monitoring ability.…”
Section: Introductionsupporting
confidence: 89%
“…These findings clarify prior work identifying an increase in metacognitive bias in aversive contexts [29], and provide support for our assertion that approach and avoidance motivations underlie differences previously attributed to context. Because our design improved accuracy-demand trade-offs through deterministic state transitions, our results are also consistent with recent work showing higher decision confidence is associated with model-free learning when model-based and model-free systems have chance level performances [30]. In this study, reduced metacognitive bias was associated with more model-based control and faster learning rates.…”
Section: Plos Computational Biologysupporting
confidence: 91%
“…Because we chose to improve accuracy-demand trade-offs through deterministic state transitions, our results are also consistent with recent work showing higher decision confidence is associated with model-free learning when model-based and model-free systems have chance level performances. 27 In this study, better metacognitive accuracy was associated with more model-based control and faster learning rates. Thus, model-based actions can be interpreted to reflect explicit forecasts.…”
Section: Discussionmentioning
confidence: 51%